Sifonóforos (Cnidaria) de aguas superficiales del mar Caribe mexicano (1991) - Gasca, Rebeca (1999)
A total of 26 species of Siphonophora were collected near the surface layer (0-3 m) al 25 sampling sites during four oceanographic cruiscs carried out in February, March, May and August 1991 in the Mexican Caribbean Sea. Plankton trawls were performed during day and night, in oceanic and neritic waters. Highest siphonophore densities were recorded in February (2067 org./1000 m3 ) and lowest in August (1226). The species composition fóund agrees, in general, with that previously reported in the 0-200 m layer. The most abundant species during the surveyed period were Abylopsis eschscholtzi, with a mean density of 433 org./1000 m3, followed by Chelophyes appendiculata (431) and by Diphyes bojani (394). None of the remaining species recorded showed densities over 90. Diphyes bojani was confirmed as consistently more abundant than D. dispar in the Caribbean, while this relation is inverse in the Gulf of Mexico. Abylopsis eschscholtzi and C. appendiculata dominated particularly during the dry season, when the other common species decreased. The neritic Muggiaea kochi was collected far offshore possibly as a result of the intense mixing process of the area. Mean diversities/cruise values varied between 2.32 y 3.04, and were similar to those previously recorded in the zone.